2020
DOI: 10.1016/j.neurobiolaging.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential annualized rates of hippocampal subfields atrophy in aging and future Alzheimer's clinical syndrome

Abstract: Several studies have investigated the differential vulnerability of hippocampal subfields during aging and Alzheimer's disease (AD). Results were often contradictory, mainly because these works were based on concatenations of cross-sectional measures in cohorts with different ages or stages of AD, in the absence of a longitudinal design. Here, we investigated 327 participants from a population-based cohort of non-demented older adults with a 14-year clinical follow-up. MRI at baseline and 4 years later were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…The hippocampus is critical for cognitive functions and is one of the most vulnerable brain regions to aging and implicated in age-related cognitive decline (Small et al, 2011). Moreover, emerging evidence has pointed to a differential vulnerability of hippocampal subfields in aging and neurodegenerative diseases (Fu et al, 2018; Morrison and Baxter, 2012; Roussarie et al, 2020), being the dentate gyrus particularly affected during normal aging (Morrison and Baxter, 2012; Nadal et al, 2020). Although most of these studies have focused on neuronal populations, recent findings have suggested that major changes in the gene expression profile of glial cells, especially astrocytes, might predict and/or impact the selective vulnerability of brain regions to aging-associated cognitive decline (Boisvert et al, 2018; Clarke et al, 2018; Soreq et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is critical for cognitive functions and is one of the most vulnerable brain regions to aging and implicated in age-related cognitive decline (Small et al, 2011). Moreover, emerging evidence has pointed to a differential vulnerability of hippocampal subfields in aging and neurodegenerative diseases (Fu et al, 2018; Morrison and Baxter, 2012; Roussarie et al, 2020), being the dentate gyrus particularly affected during normal aging (Morrison and Baxter, 2012; Nadal et al, 2020). Although most of these studies have focused on neuronal populations, recent findings have suggested that major changes in the gene expression profile of glial cells, especially astrocytes, might predict and/or impact the selective vulnerability of brain regions to aging-associated cognitive decline (Boisvert et al, 2018; Clarke et al, 2018; Soreq et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem studies provide evidence of neuronal loss of the dentate gyrus, subiculum and CA1 in the range of 32-67% across the lifespan (Simić et al 1997;West et al 1994). Voxel-based morphometry (VBM) analysis of structural MRI has sometimes agreed with this, nding reduced volume in the subiculum in ageing (Chételat et al 2008;La et al 2010;Thomann et al 2013), but the sub elds implicated vary widely across studies (Nadal et al 2020;Olsen et al 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Advances in MRI spatial resolution and automated segmentation algorithms using ultra-high resolution ex-vivo MRI reference templates (Iglesias et al 2015), have allowed increasingly precise estimation of the volume of the sub elds. It is now evident that sub elds are differentially impacted across neurological diseases (Nadal et al 2020) suggesting selective vulnerabilities to different pathologies with varying phenotypic outcomes. Examination of the effects of age across the entire hippocampus may mask non-linear trajectories that re ect some of the unique properties of hippocampal sub elds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, the hippocampal formation consists of multiple, lamellar subdivisions organized along the longitudinal axis of hippocampus, including cornu ammonis 1 (CA1), CA3, CA4, dentate gyrus (DG) and subiculum 4 – 6 . Hippocampal subfields have been reported to be differentially vulnerable to a variety of disorders, including autism, Alzheimer’s disease, schizophrenia, and bipolar disorder 7 12 , as well as prodromal disease states and in individuals clinically normal, yet at-risk for disease 13 15 .…”
Section: Introductionmentioning
confidence: 99%